Cystic fibrosis: current concepts - Jaime A. López-Valdez; Luis A. Aguilar-Alonso; Vanessa Gándara-Quezada; Gabriel E. Ruiz-Rico; Juana M. Ávila-Soledad; Adriana A. Reyes; Fernando D. Pedroza-Jiménez (Permanyer, 2021)
Cystic fibrosis is an autosomal recessive genetic disease, mainly in Caucasian children and young adults. It is caused by pathogenic variants in the CFTR (cystic fibrosis transmembrane conductance regulator) gene, which results in increased viscosity and difficult mucus clearance. The main organ affected is the lung, the pancreas, sweat glands, intestine, liver, nasal mucosa, salivary glands, and reproductive tract. The clinical manifestations vary, ranging from the most frequent pulmonary symptoms of obstructive disease to gastrointestinal manifestations related to malabsorption secondary to pancreatic insufficiency. Although there are multiple diagnostic tests for cystic fibrosis, neonatal screening to identify increased immunoreactive trypsinogen, chloride sweat test, and the detection of pathogenic variants in the CFTR gene allow the diagnosis to be integrated. Cystic fibrosis management consists of three main strategies: firstly, to keep the airway free of secretion; secondly, to keep the airway free of infection; and finally, to maintain an optimal nutritional status. Therapies that seek to correct alterations in the CFTR gene are focused on avoiding a pathogenic nonsense variant, correcting folding, increasing trafficking to the plasma membrane, or increasing the function of the CFTR channel. Other therapies still under development include gene therapy, genome editing, and antisense oligonucleotides to modify the expression of this gene.